Surveillance - World Bank (Washington, DC, 2012)
Health surveillance is the ongoing systematic collection, analysis and interpretation of health data essential for planning, implementing, and evaluating public health activities, closely integrated with timely dissemination of the data to enable effective and efficient action to be taken to prevent and control disease. The scope of surveillance is broad, from early warning systems for rapid response in the case of communicable diseases to planned response in the case of non-communicable diseases, where the lag time between exposure and disease is longer than for communicable diseases. Most countries have laws or regulations on mandatory reporting of a list of conditions determined by each country, primarily communicable diseases such as childhood vaccine-preventable diseases (polio, measles, tetanus, and diphtheria), TB, hepatitis, meningitis, and leprosy. Relatively small investments can be very effective in reducing death, disease, and disability. Surveillance can make the health system more effective and efficient, and better able to control devastating epidemics. It can lead to early detection of local epidemics when control is more effective, less costly, and involves less loss of life. Surveillance is also important for controlling and preventing endemic diseases that reduce productivity and can be costly to manage. Good surveillance systems permit early identification of diseases such as TB and syphilis that can be cured easily with low-cost treatments, combined with other public health actions.